Internalization of art value of syarafal anam adults characters building - Naser, Muhammad Nikman; Budrianto, Budrianto (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
Teenagers always want to try new things, but there is a gap between their desires and the demands of society. The thinking of adolescents who are still unstable requires values that become their benchmarks for behaviour so that they become adolescents with character. The purpose of this research is to study and analyze the values contained in the syarafal anam culture which can later be transformed into the adolescent generation and applied in counselling guidance services. This research is an ethnographic study, the data analysis used is the composition analysis. The results of the study found that in syarafal cultural activities there are values of a religious character, creativity, fondness of reading and friendship.